Comparability of family planning quality of care measurement tools in low-and-middle income country settings: a systematic review - Elizabeth Hazel; Diwakar Mohan; Margaret Gross; Sushama Kattinakere Sreedhara; Prakriti Shrestha; Maia Johnstone; Melissa Marx (BMC, 2021)
Plain language summary Accurate measures of process quality of care-or how well clinicians deliver services according to standards of care-are important to monitor, evaluate and improve service quality. Periodic surveys of health facilities or provider are the main source of national or regional quality of care data in many low- and middle-income countries. Many tools are used for these surveys: exit interviews with patients, observations of the visits by a clinician-assessor, simulated or mystery patients, and others. Implementers must select the appropriate and feasible tools for their program, context and setting but there is little information on how well different tools measure the same quality of care indicators. This review summarizes the current literature on the validity of measurements from different family planning quality of care tools. We found only eight studies, but we were able to see some differences important to consider when selecting the most appropriate tool. For instance, patients reported different events through an exit interview than what was documented by the assessor during the same visit. Exit interviews may be more appropriate to measure client experience or satisfaction rather than specifics of the care received. Knowing these differences will help implementers choose an appropriate tool depending on the focus of the quality assessment. This review contributes to the body of knowledge on improving quality of care measurements, resulting in better data to improve family planning services for patients.